O cheiro triste das bergamotas - Castro, Guilherme Azambuja (2014)
"O cheiro triste das bergamotas" is a dissertation on Creative Writing, and consists of a literary work (short stories) followed by a theoretical essay about the author process of creation: his notes, which covers the following areas: voice, transcendence, experience and observation, autonomy, point of view, dialogue, identity, sphericity, and plot. The dissertation is also comprised of an attachment to the history of writing stories.